Constructal law in energy transport and utilization - Gunes, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Economies around the world are greatly affected by global transport. The movement of freight between starting and end points can occur in numerous different ways that each have their own unique positive and negative aspects. While studies on transportation need to involve optimization, this alone is insufficient due to how any specific optimization only applies to an optimal value for a specific time period. Transportation models have dynamic structures that necessitate having decision makers also consider how time factors into their policies. Constructal law is a method that can allow models for international transportation to be simplified by applying the results of Constructal law regarding the configuration of river deltas to the question of how best to set up a few large and many small transport modes for a given route, which in air transport can be referred to as the hub and spokes model. This article investigates a transport model based on having a small number of large and many small modes of transport and uses yearly data.
Keywords: Energy consumption; Thermodynamics; Constructal law; Marine transport; Air transport; Highway transport; Hierarchy; Economies of scale; Mechanics